Size-selective microfluidics delineate the effects of combinatorial immunotherapy on T-cell response dynamics at the single-cell level - Ayan Chatterjee; Aniket Bandyopadhyay; Tapas Kumar Maiti; Tarun Kanti Bhattacharyya (Microsystems & Nanoengineering)
Abstract Cellular communication at the single-cell level holds immense potential for uncovering response heterogeneity in immune cell behaviors. However, because of significant size diversity among different immune cell types, controlling the pairing of cells with substantial size differences remains a formidable challenge. We developed a microfluidic platform for size-selective pairing (SSP) to pair single cells with up to a fivefold difference in size, achieving over 40% pairing efficiency. We used SSP to investigate the real-time effects of combinatorial immunotherapeutic stimulation on macrophage T-cell interactions at the single-cell level via fluorescence microscopy and microfluidic sampling. While combinatorial activation involving toll-like receptor (TLR) agonists and rapamycin (an mTOR inhibitor) has improved therapeutic efficacy in mice, its clinical success has been limited. Here, we investigated immune synaptic interactions and outcomes at the single-cell level in real time and compared them with bulk-level measurements. Our findings, after tracking and computationally analyzing the effects of sequential and spatiotemporal stimulations of primary mouse macrophages, suggest a regulatory role of rapamycin in dampening inflammatory outputs in T cells.